Octanal-induced inflammatory responses in cells relevant for lung toxicity: Expression and release of cytokines in A549 human alveolar cells. (July 2014) - Song, M-K; Lee, H-S; Choi, H-S; Shin, C-Y; Kim, Y-J; Park, Y-K; Ryu, J-C
Inhalation is an important route of aldehyde exposure, and lung is one of the main targets of aldehyde toxicity. Octanal is distributed ubiquitously in the environment and is a component of indoor air pollutants. We investigated whether octanal exposure enhances the inflammatory response in the human respiratory system by increasing the expression and release of cytokines and chemokines. The effect of octanal in transcriptomic modulation was assessed in the human alveolar epithelial cell line A549 using oligonucleotide arrays. We identified a set of genes differentially expressed upon octanal exposure that may be useful for monitoring octanal pulmonary toxicity. These genes were classified according to the Gene Ontology functional category and Kyoto Encyclopedia of Genes and Genomes analysis to explore the biological processes related to octanal-induced pulmonary toxicity. The results show that octanal affects the expression of several chemokines and inflammatory cytokines and increases the levels of interleukin 6 (IL-6) and IL-8 released. In conclusion, octanal exposure modulates the expression of cytokines and chemokines important in the development of lung injury and disease. This suggests that inflammation contributes to octanal-induced lung damage and that the inflammatory genes expressed should be studied in detail, thereby laying the groundwork for future biomonitoring studies.